A co-culture system with cumulus oophurus cells improves the quality of bovine embryos produced in vitro - Guevara-Chacón, Susana (2020)
The aim of this study was to determine the influence of a co-culture system with cumulus oophorus cells on the quality of bovine embryos produced in vitro, based on their viability. Ovaries from crossbred bovine slaughtered at the Chachapoyas Municipal Benefit Centre, Amazonas, Peru, were used. Oocytes aspirated from 2-6 mm follicles were matured in TCM-199 medium for 24 hours, in a humidified atmosphere with 6% CO2 and 38.5 °C. The maturation state was determined by the nuclear stage through aceto-orcein staining. The mature oocytes were fertilized in vitro with frozen semen from Angus bulls for 18 hours. The presumed zygotes were randomly distributed for development in one group in medium with co-culture and another in medium without co-culture (control). The embryonic quality was determined based on the enzymatic activity and DNA damage of the embryos on the seventh day of culture, using the fluorochromes fluorescein diacetate (FDA) and propidium iodide (PI), respectively. No significant association (p>0.05) was found in the number of embryos produced in vitro, but there was a significant difference in embryonic viability in favour of the system with co-culture (p<0.05). The use of co-cultures with cumulus oophurus cells improves viability and, therefore, embryonic quality, without influencing the rate of embryo production in vitro.